Tumor-Homing Glycol Chitosan-Based Optical/PET Dual Imaging Nanoprobe for Cancer Diagnosis - Lee, Sangmin; Kang, Sun-Woong; Ryu, Ju Hee; Na, Jin Hee; Lee, Dong-Eun; Han, Seung Jin; Kang, Choong Mo; Choe, Yearn Seong; Lee, Kyo Chul; Leary, James F.; Choi, Kuiwon; Lee, Kyung-Han; et al. (AMER CHEMICAL SOC, 2014)
Imaging techniques including computed tomography, magnetic resonance imaging, and positron emission tomography (PET) offer many potential benefits to diagnosis and treatment of cancers. Each method has its own strong and weak points. Therefore, multimodal imaging techniques have been highlighted as an alternative method for overcoming the limitations of each respective imaging method. In this study, we fabricated PET/optical activatable imaging probe based on glycol chitosan nanoparticles (GNPs) for multimodal imaging. To prepare the dual PET/optical probes based on CNPs, both Cu-64 radiolabeled DOTA complex and activatable matrix metalloproteinase (MMP)-sensitive peptide were chemically conjugated onto azide-functionalized CNPs via bio-orthogonal click chemistry, which was a reaction between azide group and dibenzyl cyclooctyne. The PET/optical activatable imaging probes were visualized by PET and optical imaging system. Biodistribution of probes and activity of MNIP were successfully measured in tumor-bearing mice.
Keywords: FREE CLICK CHEMISTRY; MATRIX METALLOPROTEINASES; IN-VIVO; MULTIFUNCTIONAL NANOPARTICLES; CATHEPSIN-B; REAL-TIME; DELIVERY; THERAPY; PARTICLES; MICROPET